A Survey of Critical Thinking Skills of Faculty Members of Ahvaz Jundishapur University of Medical Sciences, 2020 - Shakurnia, Abdolhussein; Khajeali, Nasrin; Sharifnia, Reza (International Journal of Education and Cognitive Sciences, 2022)
Background and purpose: One of the important tasks of faculty, in addition to transferring knowledge and skills to learners, is to train students as thoughtful, analytical and critical thinking individuals. The need for critical thinking in medical education in response to the rapidly changing health care environment has been emphasized. One of the main tasks of any medical educational institution, in addition to developing students' professional competencies, is to develop decision-making, problem-solving and self-efficacy skills, which are themselves influenced by the ability to practice critical thinking. The aim of this study was to investigate the critical thinking of the faculty members of the medical school of Ahvaz Jundishapur University of Medical Sciences in 2020.Materials and Methods: This is a descriptive-analytical study. The sample consisted of 53 faculty members of the medical school of the University of Medical Sciences. The data collection tool was the California Critical Thinking Questionnaire Form B. Independent t-test and Pearson correlation were used to analyze the data.Results: The mean score of faculties' critical thinking skills was 12.53, which is lower than the average score in the standardization process (15.89). Other findings showed that there is no statistically significant difference between critical thinking and gender, age and academic rank of professors.Conclusion: The results of the study indicate the weakness of faculties' critical thinking in critical thinking and all its dimensions, which indicates the need to teach critical thinking skills at the university level.